LCAS-APT Protocol (Landscape Crop Assessment Survey and Agronomy Prioritization Tool) Version 0.1 - Urfels, Anton; Assefa, Banchayehu; Silva, João Vasco; Aubert, Celine; Samaddar, Arindam; Ajay, Anurag; Schmitter, Petra S.; Senthilkumar, Kalimuthu; Kumar, Virender; McDonald, Andrew J.; Vanlauwe, Bernard (International Rice Research Institute, 2024)
The Landscape Crop Assessment Survey (LCAS) and Agronomy Prioritization Tool (APT) is an agricultural data collection and analytics tools that use a lean data approach, focusing on recurrently collecting essential data on crop production practices to drive impactful decision-making in smallholder farming systems, enhance agricultural practices, and tackle productivity and sustainability challenges in diverse farming landscapes.